2009
DOI: 10.1371/journal.pone.0004653
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide and Candidate Gene Association Study of Cigarette Smoking Behaviors

Abstract: The contribution of common genetic variation to one or more established smoking behaviors was investigated in a joint analysis of two genome wide association studies (GWAS) performed as part of the Cancer Genetic Markers of Susceptibility (CGEMS) project in 2,329 men from the Prostate, Lung, Colon and Ovarian (PLCO) Trial, and 2,282 women from the Nurses' Health Study (NHS). We analyzed seven measures of smoking behavior, four continuous (cigarettes per day [CPD], age at initiation of smoking, duration of smok… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
180
1
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 232 publications
(194 citation statements)
references
References 85 publications
11
180
1
1
Order By: Relevance
“…However, recent methodological studies (Morey et al, 2009;Jovicich et al, 2009) have demonstrated that Freesurfer can be considered an acceptable substitute for manual tracing of automatically quantified amygdala volume, although a large cohort of subjects is warranted. Second, the lack of a significant association between amygdala volume and MAO A VNTR polymorphism could be influenced by further social/psychological variables not taken into consideration in this work, such as impulsivity (Soloff et al, 2008), social disadvantage experiences such as trauma or abuse history (Caspi et al 2002, Kim-Cohen et al 2006 or cigarette smoking behaviour (Caporaso et al, 2009) that could ultimately interact with MAO A functioning. In particular, the association between variants in MAO gene region and cigarette smoking behaviour is notable because of the role of the monoamine oxidases in the regulation of catecholamines and the inhibition of MAO A and B by tobacco smoke (Fowler et al, 2003).…”
Section: Discussionmentioning
confidence: 98%
“…However, recent methodological studies (Morey et al, 2009;Jovicich et al, 2009) have demonstrated that Freesurfer can be considered an acceptable substitute for manual tracing of automatically quantified amygdala volume, although a large cohort of subjects is warranted. Second, the lack of a significant association between amygdala volume and MAO A VNTR polymorphism could be influenced by further social/psychological variables not taken into consideration in this work, such as impulsivity (Soloff et al, 2008), social disadvantage experiences such as trauma or abuse history (Caspi et al 2002, Kim-Cohen et al 2006 or cigarette smoking behaviour (Caporaso et al, 2009) that could ultimately interact with MAO A functioning. In particular, the association between variants in MAO gene region and cigarette smoking behaviour is notable because of the role of the monoamine oxidases in the regulation of catecholamines and the inhibition of MAO A and B by tobacco smoke (Fowler et al, 2003).…”
Section: Discussionmentioning
confidence: 98%
“…Most prominent among these are the human genetic association studies showing that single nucleotide polymorphisms in the gene cluster CHRNA5/Α3/Β4, encoding for the α3, α5, and β4 nAChR subunits, are closely associated with the risk for heavy smoking, inability to quit, and increased sensitivity to nicotine. [7][8][9][10][11] Further, studies in knockout mice show that the β4 nAChR subunit is necessary for nicotine withdrawal because withdrawal is greatly diminished in β4 null mice, but not in β2 null mice. 12,13 Unlike the wide distribution of α4β2 nAChR in the brain, the α3 and β4 subunits are expressed in a restricted number of brain areas, mainly the medial habenula and interpeduncular nucleus, major cholinergic tracts in the brain that have recently garnered increasing attention for their involvement in various aspects of nicotine dependence.…”
Section: Introductionmentioning
confidence: 99%
“…Another, not mutually exclusive, possibility is that individuals with one or more copies of the T-allele may be more resistant to the aversive side effects of nicotine (Munafo et al 2011). Interestingly, it is the T-allele of the rs1051730 polymorphism which has been repeatedly associated with nicotine dependence (Berrettini et al 2008;Bierut et al 2008;Caporaso et al 2009;Saccone et al 2009). Moreover, there is evidence for an association between the T-allele of the rs1051730 polymorphism and decreased likelihood of smoking cessation (Munafo et al 2011) -further emphasizing the role of the T-allele in the context of nicotine dependence and smoking behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, our previous results indicate that there might be shared variance in the molecular genetic substrates for both nicotine dependence and sensorimotor gating: interestingly, the CHRNA3 rs1051730 T allele and the rs1317286 G allele have been firmly established as risk alleles for nicotine dependence (Berrettini et al 2008;Bierut et al 2008;Caporaso et al 2009;Saccone et al 2009). Probably, a genetically induced alteration in the nAChR-system is (in part) responsible for both deficits in sensorimotor gating and increased risk for smoking.…”
Section: Introductionmentioning
confidence: 95%